Variability in Marine Plankton Ecosystems Are Not Observed in Freshly Emitted Sea Spray Aerosol Over the North Atlantic Ocean. Issue 1 (17th January 2020) - Bates, T. S.; Quinn, P. K.; Coffman, D. J.; Johnson, J. E.; Upchurch, L.; Saliba, G.; Lewis, S.; Graff, J.; Russell, L. M.; Behrenfeld, M. J.
Abstract: Sea spray aerosol (SSA) consists of both sea salt and organic components. These aerosols affect Earth's climate by scattering solar radiation and by altering cloud properties. Here we present observations of SSA particles generated at sea using an over‐the‐side bubbling system (Sea Sweep) and an onboard plunging wave mesocosm (Marine Aerosol Reference Tank—MART) during five cruises in the North Atlantic. The cruises were timed to sample different stages of the North Atlantic plankton bloom and included transects from the oligotrophic Sargasso Sea to the biologically productive western subarctic. The results show that the North Atlantic plankton bloom has little effect on the emission flux, organic fraction, or cloud condensation nuclei (CCN) activity of SSA, and therefore, plankton ecosystems do not need to be included in modeling aerosol indirect effects of primary SSA in global climate models or in chemical transport models. Plain Language Summary: Breaking waves on the ocean surface emit sea spray aerosol (SSA) to the atmosphere. These particles affect Earth's climate by scattering solar radiation and altering cloud properties (e.g., cloud brightness, extent, and rain). SSA consists of both sea salt and organic components. A key question in chemical transport and climate models is whether marine plankton ecosystems affect the organic component of SSA. The results presented here show that marine plankton ecosystems have little effect on SSA and that the ocean source of organic SSA comes from the large pool of dissolved organic carbon in the ocean. Chemical transport and climate models, therefore, can treat the ocean as a uniform organic SSA source, affected only by sea surface temperature. Key Points: Marine plankton ecosystems do not directly affect sea spray aerosol Chemical transport and climate models do not need to incorporate plankton ecosystems in modeling sea spray aerosol